Aspects and assessment of delirium in old age First data from a German interdisciplinary emergency department - Singler, K.; Thiem, U.; Christ, M.; Zenk, Philipp; Biber, R.; Sieber, Cornel; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2014)
The prevalence of delirium in hospitalized patients is high, but delirium is frequently not identified by treating physicians in emergency departments (EDs). Although the number of elderly patients admitted to EDs is increasing, no data on prevalence, identification and outcome of delirious elderly patients in German EDs exist.To evaluate the prevalence and identification of delirium in elderly patients in a German ED and to identify characteristics of delirium in elderly ED patients.Evaluation of data from a prospective single-center observational study. The study was conducted in the interdisciplinary ED of an urban university-affiliated hospital receiving approximately 80,000 visits per year. The shortened Confusion Assessment Method (CAM) was used to screen 133 consecutive ED patients, aged 75 years and older, for delirium. Comorbid conditions were ascertained by patient interview and review of medical records. Data concerning patient mortality and current living status were collected 28 days after the ED visit in a structured telephone interview.A positive CAM result was recorded in 14.3 % of cases; 68.4 % of these CAM-positive patients were not identified as being delirious by the ED physician. The 28-day mortality was higher among patients with delirium. Dependency on external help, polypharmacy, pre-existing cognitive or mobility impairments and the presence of any care level were strongly associated with delirium.Elderly patients with known risk factors should be routinely assessed for delirium in the ED with a standardized assessment tool such as the CAM.
Keywords: Geriatric; Confusion Assessment Method; Polypharmacy; Cognitive impairment; Screening

Aspects and assessment of delirium in old age. First data from a German interdisciplinary emergency department - Singler, K.; Thiem, U.; Christ, M.; Zenk, Philipp; Biber, R.; Sieber, Cornel; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2014)
The prevalence of delirium in hospitalized patients is high, but delirium is frequently not identified by treating physicians in emergency departments (EDs). Although the number of elderly patients admitted to EDs is increasing, no data on prevalence, identification and outcome of delirious elderly patients in German EDs exist.To evaluate the prevalence and identification of delirium in elderly patients in a German ED and to identify characteristics of delirium in elderly ED patients.Evaluation of data from a prospective single-center observational study. The study was conducted in the interdisciplinary ED of an urban university-affiliated hospital receiving approximately 80,000 visits per year. The shortened Confusion Assessment Method (CAM) was used to screen 133 consecutive ED patients, aged 75 years and older, for delirium. Comorbid conditions were ascertained by patient interview and review of medical records. Data concerning patient mortality and current living status were collected 28 days after the ED visit in a structured telephone interview.A positive CAM result was recorded in 14.3 % of cases; 68.4 % of these CAM-positive patients were not identified as being delirious by the ED physician. The 28-day mortality was higher among patients with delirium. Dependency on external help, polypharmacy, pre-existing cognitive or mobility impairments and the presence of any care level were strongly associated with delirium.Elderly patients with known risk factors should be routinely assessed for delirium in the ED with a standardized assessment tool such as the CAM.
EVALuna2:10531